Penggunaan Video Screencast O-Matic Pada Mata Kuliah Aljabar Abstrak - Enny Listiawati (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2018)
In the millennial era an innovative and creative learning media is needed by utilizing technology that can improve the quality of student learning in abstract algebra lectures. One of them is by using Screencast O-Matic (SOM) software application. SOM is software that is generally used for making tutorial videos to explain or explain learning material.The purpose of this study was to determine the effectiveness of the use of SOM in abstract algebra learning in terms of student activity and completeness of student learning outcomes. The subjects of this study were the 5th semester students of the 5th semester Mathematics education program at STKIP Bangkalan PGRI who were participating in the Abstract Algebra course. 35 students. This type of research is quantitative descriptive, with the research instruments being the observation sheet of student activities and learning outcomes test questions. The results of this study are the use of Screencast O-matic software media in learning abstract algebra courses said to be effective based on indicators of effectiveness consisting of effective student activities and student learning outcomes completed in a classical manner.